The association between junior tennis players` physical and cognitive attributes and groundstroke performance - Turner, M.; Russell, A.; Turner, K.; Beranek, P.; Joyce, C.; McIntyre, F.; Cruickshank, T. (International Journal of Sports Science & Coaching, 2023)
Improving groundstroke velocity and accuracy is critical for tennis success. However, there is limited research available on the physical and cognitive attributes required for groundstroke performance. Therefore, the purpose of this study was to investigate the physical and cognitive characteristics and their association with groundstroke performance in junior tennis players. Thirty-four competitive junior tennis players, aged 12.59 ± 2.44 years, participated in this cross-sectional study. Cognitive tests assessing processing speed, complex attention, cognitive flexibility and problem-solving capacity and physical tests assessing flexibility, speed, agility, power, strength and anaerobic and aerobic capacity were performed. Tennis groundstroke performance was evaluated using a novel tennis groundstroke assessment. Tennis groundstroke performance was associated (p < 0.05) with the number of hours a participant practices per week, their ranking, lower and upper body power, tennis agility test (decision and total time), linear speed, upper body strength and aerobic capacity. Specifically, an estimated 83.76% of the groundstroke velocity accuracy index variability was explained by grip strength in the dominant hand and ranking. An estimated 79.63% of the groundstroke velocity accuracy error index variability was explained by the number of hours a participant practices per week and their ranking. Our study showed an association between tennis groundstroke performance and physical but not cognitive outcomes in junior tennis players. Specific attention should be dedicated to developing the upper body strength of junior tennis players for improved groundstroke velocity and accuracy. This knowledge can assist tennis coaches in planning effective training sessions.